1993
DOI: 10.1071/ch9931909
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Chemical Reactivity in Some Benzo[b]Naphthyridines (Azaacridines)

Abstract: Some comparisons between four series of benzo [b][1,x] naphthyridines (x=5-8) have been made. Bromination in acetic acid gave almost exclusive reaction β to the nitrogen in the outer pyrido ring. Basic silver oxide oxidation of the centre ring occurred in the order x = 6 > 8 > 7 > 5. Methylation occurred on the pyrido nitrogen, the relative nucleophilicities paralleling those of the corresponding naphthyridines . One methiodide (x = 6) underwent an interesting dimerization in solution and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These products react with DMSO and trifluoromethanesulfonic anhydride giving rise to S,Sdimethyl-[N(1),N(i )-naphthyridin-2-yl]sulfylimines 64a ± c. 115 The kinetics of N-methylation of benzonaphthyridines 65a ± d with methyl iodide in DMSO have been studied. 117 It was shown that the salt 66, formed from the naphthyridine 65b, slowly dimerises in a 10% aqueous solution of DMSO to give compound 67.…”
Section: The Reactivity Of Naphthyridinesmentioning
confidence: 99%
“…These products react with DMSO and trifluoromethanesulfonic anhydride giving rise to S,Sdimethyl-[N(1),N(i )-naphthyridin-2-yl]sulfylimines 64a ± c. 115 The kinetics of N-methylation of benzonaphthyridines 65a ± d with methyl iodide in DMSO have been studied. 117 It was shown that the salt 66, formed from the naphthyridine 65b, slowly dimerises in a 10% aqueous solution of DMSO to give compound 67.…”
Section: The Reactivity Of Naphthyridinesmentioning
confidence: 99%